DEVELOPMENT OF THE CREATIVE POTENTIAL OF FUTURE QUALIFIED WORKERS IN VOCATIONAL EDUCATION INSTITUTIONS: - - Popovych, Olesya; Tarasova, Olena (Professional Pedagogics, 2023)
Relevance: the request of society and the economy for training of creative, ambitious and innovative thinking specialists in vocational (vocational education and training) education institutions (hereinafter – V(VET)E), namely, the specialists who are able to ensure the rapid recovery of the war-ravaged economy of Ukraine and the further sustainable development of society. Purpose: to carry out a theoretical analysis of the existing scientific views on the development of the creative potential of education seekers who receive work qualifications in V(VET)E institutions, as well as to determine and substantiate the necessary psychological and pedagogical conditions for this. Methods: pedagogical observation – to determine the conditions for the successful realization of the creative potential of education seekers; theoretical analysis of scientific and scientific-methodical literature – to establish the characteristic features of creative potential; generalization, deductive, inductive, logical – to identify rational ways and methods of identifying the creative potential of education seekers. Results: the psychological and pedagogical conditions for the development of the creative potential of future qualified workers in V(VET)E institutions are identified and characterized. Conclusions: the most common views of scientists on the development of the creative potential of future specialists in V(VET)E institutions are analyzed and the psychological and pedagogical conditions necessary for successful implementation are determined (increasing their motivation during the acquisition of professional competences; strengthening the connection between the theoretical and practical components of the educational material; ensuring the interaction of all participants in the educational process on an equal, democratic basis).